Continuous reactive crystallization of β-lactam antibiotics catalyzed by penicillin G acylase. Part II: Case study on ampicillin and product purity. (12th July 2019) - McDonald, Matthew A.; Bommarius, Andreas S.; Grover, Martha A.; Rousseau, Ronald W.
Highlights: Crystal purity in continuous enzymatic ampicillin production and crystallization. Multiple steady states in well-mixed reactive crystallizer. Well-mixed and plug flow reactive crystallizer series gives high yield and purity. Developed process purity robust to parameter and operational variability. Abstract: Continuous reactive crystallization of β-lactam antibiotics can ease shortage and contamination concerns for an important class of medicines. With a model of continuous reactive crystallization catalyzed by penicillin G acylase (PGA), a process is developed to ensure purity of the antibiotic product. Guaranteeing the solid-phase purity of ampicillin and cephalexin is important because PGA produces a slightly soluble byproduct, phenylglycine, which can contaminate the antibiotic crystals. In a single well-mixed reactive crystallizer, productivity is optimized and nearly two-fold greater than the non-crystallizing maximum productivity. Process robustness is essential because multiple steady states, only one of which produces pure ampicillin crystals, exist in the well-mixed reactive crystallizer. By combining well-mixed and plug-flow reactive crystallizers in series, crystallization of phenylglycine can be suppressed while high yield and comparable productivity are still achieved. The reactive crystallizer series demonstrates high purity with uncertainty in model parameter values and variability in operating conditions.